Psychometric properties of the Oswestry Disability Index. Issue 3 (September 2017) - Saltychev, Mikhail; Mattie, Ryan; McCormick, Zachary; Bärlund, Esa; Laimi, Katri
Abstract : The aim of this study was to investigate the psychometric properties of the Oswestry Disability Index (ODI) in a large cross-sectional cohort of individuals with chronic low back pain by defining its internal consistency, construct structure and validity, and its ability to differentiate between different degrees of functional limitation. A total of 837 consecutive outpatient patients with low back pain were studied. The internal consistency of ODI was assessed by Cronbach's α, construct structure by exploratory factor analysis, construct validity by confirmatory factor analysis, and discrimination was determined by item response theory analysis. The ODI showed good internal consistency ( α =0.85). Explanatory factor analysis showed that ODI is a unidimensional test measuring functional level and nothing else. The confirmatory factor analysis showed that the standardized regression weights of all ODI items were relatively high, varying from 0.5 to 0.7. The item response theory analysis suggested that eight out of 10 ODI items have a close to perfect ability to measure functional limitations in accordance with the actual severity of disability experienced by the respondents. Discrimination of all the items was high to perfect (1.08–2.01). The test characteristic and test information curves showed that the discriminative ability of the ODI is superior at higher levels of disability. The present data showed that the ODI is an internally consistent, unidimensional scale with overall excellent construct validity and ability to discriminate the severity of functional disability. The analysis suggests that the ODI may better distinguish between the relative degrees of function at above-average disability levels.